Belle’s characterization as the main character in Beauty and The Beast movie by Bill Condon - Putriwana, Nadia Ayu; Yustisia, Karlina Karadila (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
This study defines the characterization of the main character in the Beauty and the Beast movie in 2017 directed by Bill Condon. The main character in this movie is Belle, a daughter of Maurice who is an inventor in Villeneuve, a small town in France. The movie tells about a love story between the cursed prince who turns into a Beast and a beautiful village girl. This study aimed to find out the characterizations of Belle, the most dominant character in the movie. All characterization could be described through appearances, dialogues, personal descriptions, reactions of other characters, actions, and speeches. From the analysis, it is found that the protagonist Belle, not only described as kind, brave, smart, creative, assertive, and loyal but also, a free thinker loner who can be assertive and even judmental. Afterall, Belle the leading female character in Disney's Beauty the Beast, is one of the most beloved and recognized Disney princesses. She is beautiful, motivating, loving, and strong, just like her royal peers.DOI: 10.26905/enjourme.v6i1.6131